2006
DOI: 10.1007/bf03021849
|View full text |Cite
|
Sign up to set email alerts
|

Morphine overdose from error propagation on an acute pain service

Abstract: Purpose: To highlight a case in which multiple errors occurred during programming and administration of analgesia via a patient-controlled analgesia (PCA) pump, and to formulate recommendations on how to avoid such errors in the future. Clinical features:Following lumbar surgery, a 43-yr-old woman was switched from epidural analgesia to a PCA pump. This change was associated with numerous errors at several points of delivery of her care. Errors included incorrect connection of the PCA adapter, incorrect pump p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…Hankin et al [23] reported on device-associated adverse events and found that with PCAs, device malfunction was a major cause of reported adverse events but operator errors were more likely to be associated with adverse outcomes. Various case reports reiterate the adverse outcomes associated with operator/programming errors [24][25][26][27]. Our findings did not have any device malfunction as a cause of CIs.…”
Section: Prevention Of Ciscontrasting
confidence: 52%
“…Hankin et al [23] reported on device-associated adverse events and found that with PCAs, device malfunction was a major cause of reported adverse events but operator errors were more likely to be associated with adverse outcomes. Various case reports reiterate the adverse outcomes associated with operator/programming errors [24][25][26][27]. Our findings did not have any device malfunction as a cause of CIs.…”
Section: Prevention Of Ciscontrasting
confidence: 52%
“…This route is not without risk as evidenced by local MRAEs reports and repeated errors with preparation and administration of opioid PCA. These issues are universal and have been identified in the published literature (Syed et al 2006;Hicks et al 2008;ISMP 2008). The standardisation of PCA prescriptions, the introduction of a commercially prepared infusate and a single infusion device with imbedded safety parameters have reduced the incidence of PCArelated MRAEs.…”
Section: Discussionmentioning
confidence: 99%
“…PCA is associated with prescribing, dosing and administration errors (Syed et al 2006;Hicks et al 2008;ISMP 2008) as well as adverse events such as reactions to opioids (Hankin et al 2007). The use of pre-printed prescriptions may reduce the risk of prescribing errors, but programming errors such as the incorrect inputting of the opioid concentration result in what is known as 'inverse relationships' (ISMP 2008) can still occur.…”
Section: Intravenous Opioid Pcamentioning
confidence: 99%
“…Given that the number of patients undergoing surgery annually is about 100 million worldwide, respiratory depression occurs between 1 and 12 million times and it results in about 20, 000 preventable deaths each year [11]. The troublesome aspect of this complication is that it can occur in healthy patients where the family and clinical staff do not anticipate a bad outcome [12].…”
Section: Introductionmentioning
confidence: 99%